2020
DOI: 10.31635/ccschem.019.20190043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry of an Interlocked Poly[2]catenane: From Single Molecule to Bulk Gel

Abstract: Citation denotes calendar and volume year of first online publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
(44 reference statements)
0
26
0
1
Order By: Relevance
“…In addition to classic ensemble measurements, we used atomic force microscopy-based single-molecule force spectroscopy (AFM-SMFS) to directly measure the binding strength between the three different RBDs and ACE2 on a living cell, respectively 17,18 . As powerful single-molecule nanotechnology, AFM-SMFS can manipulate single molecule or molecules mechanically similar to optical and magnetic tweezers [19][20][21][22][23][24][25] . It has been widely used to study the protein mechanics and protein-protein interaction, including the interaction between spike proteins of viruses and living cells [26][27][28][29][30][31][32] .…”
Section: N501y Mutation Slowed Down the Dissociation From The Ace2 Receptormentioning
confidence: 99%
“…In addition to classic ensemble measurements, we used atomic force microscopy-based single-molecule force spectroscopy (AFM-SMFS) to directly measure the binding strength between the three different RBDs and ACE2 on a living cell, respectively 17,18 . As powerful single-molecule nanotechnology, AFM-SMFS can manipulate single molecule or molecules mechanically similar to optical and magnetic tweezers [19][20][21][22][23][24][25] . It has been widely used to study the protein mechanics and protein-protein interaction, including the interaction between spike proteins of viruses and living cells [26][27][28][29][30][31][32] .…”
Section: N501y Mutation Slowed Down the Dissociation From The Ace2 Receptormentioning
confidence: 99%
“…However, it is worth mentioning that the formation of Olympic networks has been proposed as a by-product in the polymerization of 1,2-dithianes. 26,27 The synthesis of high molecular weight poly[n]catenanes 7,28,29 is challenging, as catenane synthesis requires a ring closing step that is notoriously low yielding. 7 A common approach to low molecular weight catenanes, pioneered by Sauvage, involves the threading of a linear component (or thread) through a pre-made ring driven by metal-ligand coordination, [30][31][32][33] followed by ring closing of the thread under dilute conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] These controversial findings may be attributed to the differences in the buffer compositions and the lengths of the G-rich sequences. 34 Single-molecule force spectroscopy, a promising technique allowing constant and dynamic probing of minute forces and lengths at the single-molecule level with piconewton and subnanometer resolution, [35][36][37][38][39][40][41] has been employed to explore the intramolecular and intermolecular interactions of G-quadruplexes. 19,30,[42][43][44][45][46] Using 144 nt human telomeric G-rich sequences, Mao et al 43 reported that quadruplex-quadruplex interaction (QQI) was detected in only 5% of all G-quadruplexes, while the majority of G-quadruplexes followed the beads-on-astring model.…”
Section: Introductionmentioning
confidence: 99%